(untitled) (Revista Cocar, 2015)
Ante as transformações sociais no Estado de direitos dos sujeitos, a presença intensa da tecnologia com acesso facilitado, a ausência de disciplina no trato com o conhecimento e uma sociedade que valoriza pouco a escola como espaço de construção do conhecimento, a atuação do professor mediada pela ação de ensinar tem se apresentado como desafio na contemporaneidade, pois lhe estabelece exigências, sobretudo, quando o docente se insere em sistemas educacionais orientados pela lógica dos resultados. Desenvolvida no âmbito do Grupo de Pesquisa Ensino, Aprendizagem e Processos Educativos (GPENAPE), a pesquisa descrita neste artigo teve como objeto as exigências de maior complexidade - provocadoras dos desafios na sala de aula. O problema de pesquisa se delineia nesta questão: quais exigências e desafios (im)postos aos professores são considerados como mais complexos no contexto da sala de aula e quais são as necessidades de superação? A pesquisa objetivou compreender as exigências e os desafios (im)postos ao professor contemporâneo e as necessidades de superação. A pesquisa se fundamenta em Tardif e Lessard (2011; 2009), Saraiva e Wagner (2013), Zibetti (2004), Nóvoa (1999) e Chizzotti (1998), dentre outros. O procedimento metodológico adotado foi a entrevista semiestruturada com seis professoras dos anos iniciais do ensino fundamental de escolas públicas e privadas. Os dados foram tratados com base na análise de conteúdo pela técnica da análise temática. Os resultados mostram que as exigências e desafios contemporâneos se concentram na indisciplina, falta de acompanhamento das famílias e ausência da escola e das famílias. Os indicativos de superação são: formação continuada; convicção de que estão na profissão certa e disposição profissional para lidar com as mudanças presentes na cultura escolar numa perspectiva crítica. A iniciativa para superação precisa ser da escola. Palavras-chave: Atuação do professor; Exigências sociais; Contemporaneidade The multiple requirements and challenges (im) posts to teachers in contemporaneity: tensions experienced in the classroom " Regarding social changes in the so-called individualâ€™s state of rights, the intense presence of technology easily accessible, the lack of discipline in dealing with knowledge and a society that gives little value to the school as space for the building of knowledge, the role of the teacher mediated by the act of teaching has posed a challenge to the contemporary society, because this latter establishes requirements to the teacher, especially when he or she works in educational systems guided by the capitalist logic of results. Carried out within the Teaching, Learning and Educational Processes Research Group, the research presented here focused on the requirements of more complexity â€” which lead to challenges in the classroom. Its starting point may be outlined by this question: according to teachers, which demands and challenges (im)posed to them are more complex in the context of the classroom and which of them do require overcoming measures? The research aimed to understand the requirements and challenges contemporary teachers face and the way of overcoming them. Itâ€™s drawn from Tardif and Lessard (2011; 2009), Scott and Wagner (2013), Zibetti (2004), Nóvoa (1999) and Chizzotti (1998), among others. Semi structured interviews were the methodological procedure of choice for gathering data. Six elementary public and private schoolsâ€™ early gradesâ€™ teachers were interviewed. Data were analyzed based on content analysis approach, which means, the thematic analysis. Results show that requirements and contemporary challenges focus on indiscipline, lack of support from families, and on the absence of school and families. Overcoming such scenario requires teachers to continue their training and to be aware they are in the right place and ready to deal with changes in school culture in a critical perspective. In other words, the initiative to change the state of things has to come from within the school. Keywords: Teacher Performance; Social requirements; Contemporaneity.